The Function of contemporary travel narratives in the french, anglo and latin americas: mixing and expanding cultural identity. New York/London: Mellen Press, 2011 - Walter, Roland Gerhard Mike (2012)
Resenha do livro COTÉ, Jean-François. The Function of Contemporary Travel Narratives in the French, Anglo and Latin Americas: Mixing and Expanding Cultural Identity. New York/London: Mellen Press, 2011, 170p. BENESSAIEH, Afef. Transcultural Americas/Amériques Transculturelles. Ottawa: University of Ottawa Press, 2010, 261p.